ANALISIS PROGRAM MASTURAH JAMA’AH TABLIGH DAN IMPLIKASINYA TERHADAP KELUARGA SAMARA - Suratno Suratno; Dodi Yudo Setyawan (Fakultas Dakwah dan Komunikasi, 2019)
The realization of the sakinah mawadah warahmah (samara) family is the ideal of every family. Some parameters for the realization of such a family are a wife in a household that is 'Alimah, Zahidah,' Abidah, Murabbiyah, Khaddimah and Da'iya. Many methods can be applied to make it happen, in this study focused on the method of khuruj fisabilillah masturah jama'ah tabligh. This method jama'ah husband and wife out of the house in a few days to do da'wah and study religion specifically. By analyzing the method, it was found 79.16% increase in the number of samara family parameters achieved by the family carrying out the activity.